The Dream's Door: Educational Marginalization of Rohingya Children in Malaysia. (August 2020) - Farzana, Kazi Fahmida; Pero, Siti Darwinda Mohamed; Othman, Muhammad Fuad
In Malaysia, refugees remain mostly invisible and face various challenges in terms of protection, healthcare and education. They are often preserved as 'illegal immigrants', therefore always at risk of arrest, detention, punishment and deportation. The worse sufferers of these are the children and youth, who are also considered to be illegitimate and deprived of rights including the right to education. This is a case study of a young Rohingya refugee man whose dedication and struggles, despite his problematic identity imposed by various authorities, continue to find a way out and serve fellow refugees through a community organization. However, the dream to have an education and flourish as a full-fledged human being remains a far cry for those marginalized, underprivileged Rohingya refugees and their children. Their experience in Malaysia is far from exceptional, of the sufferings that refugees are forced to bear in many countries in South and Southeast Asia. Nonetheless, this case aims to facilitate the basic understanding of displacement, the refugee situation, international law and particularly refugee children's rights to education. It provides a deeper understanding of the root causes of Rohingya's current 'stateless' situation in Malaysia, identifies the challenges faced by a refugee community organization, refugee children's struggles and rights to education. It initiates thoughts to examine the government policies and look for alternative strategies that may benefit the refugee children as well as the national development in the long run. Dilemma : Are Rohingya in Malaysia 'refugees' or 'economic migrants'? Should the children of Rohingya be given access to education? Should Malaysia sign the 1951 Refugee Convention? Theory : Statelessness theory Type of the Case : Experience-based applied single case study Protagonist : Present Options: Malaysia can take the stand that being nonsignatory to the 1951 Refugee Convention and its 1967 protocol, it is not bound to come up with policies for refugees. By providing 'temporary' shelter to a significant number of refugees and asylum-seekers, Malaysia has done enough for the refugees. At the international level, Malaysia is considered to be sympathetic towards refugees. Refugee and asylum seekers' presence has been exerting pressure on Malaysian culture and society. In contrast, refugee and migration issues are receiving attention from the government and civil society in Malaysia. Former government has tried to adopt some policies like providing short-term work permit for a small number of registered Rohingya refugees in certain plantations and manufacturing sectors on an experimental basis to avoid social and economic risks posed by unemployed refugees. Malaysia should sign the 1951 Refugee Convention and its 1967 protocol because it is a member of the United Nations (UN) and party to many other major international human rights documents such as Convention against Torture and Other Cruel Inhuman or Degrading Treatment or Punishment (CAT) and Convention on the Rights of the Child (CRC) to name a few. Discussions and Case Questions: What are the root causes of Rohingyas' current statelessness situation and how should the Malaysian government tackle the issue? What are the challenges faced by Rohingya community organizations in integrating with the society? Should Malaysia look at improving the Rohingya children's access to education or the community should take on the responsibility?